Pengaruh Edukasi Media Video Animasi tentang Puasa terhadap Pengetahuan Pre Operatif Pasien General Anestesi di RS PKU Muhammadiyah Gamping - Muhammad Zulkifli Salim; Anita Setyowati; Tri Hapsari Listyaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
Pre-operative fasting is crucial to prevent anesthetic complications such as pulmonary aspiration. However, many patients still lack adequate understanding of pre-operative fasting guidelines, increasing the risk of complications. Animated video education is considered more effective than conventional methods in improving patient knowledge. This study aimed to determine the effect of animated video education on pre-operative fasting knowledge in patients undergoing general anesthesia at PKU Muhammadiyah Gamping Hospital. A pre-experimental one-group pretest-posttest design was used, involving 30 respondents selected through accidental sampling. Data were collected using a structured questionnaire and analyzed with the Wilcoxon Signed Rank Test. The results showed a p-value of 0.000, indicating a statistically significant improvement in knowledge after the intervention. This suggests that animated video education effectively enhances patients' understanding of pre-operative fasting. In conclusion, there is a significant effect of animated video education on pre-operative knowledge regarding fasting in patients undergoing general anesthesia at PKU Muhammadiyah Gamping Hospital. Future research is recommended to use a larger sample size to improve the validity and reliability of the findings.